SOCIAL SEMIOTIC IN COVID-19 PUBLIC SERVICES ADVERTISEMENT - Tri Sutrisna Agustia Km; Hesteria Friska Armynia Subratha (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2021)
The role of an advertisement in influencing people's perceptions and understanding has its own competence in the world of marketing. Advertising can be used as one of the most appropriate promotional tools in the introduction and understanding of a concept or an invitation to do something. The persuasive matter in this research regarding the importance of the role of the community in the Covid-19 pandemic conditions. Advertising products taken in this study are several public servicess about Covid-19 from several commercial and non-commercial institutions in Bali. The phenomenon of miss-interpretation and the mismatch of the desired meaning in an advertisement has a significant impact on the development of the Covid-19 case in Bali. The purpose of this research is to align the problem of conveying a meaning in advertisements for public servicess about Covid-19 which are often not understood by the public so that there is a misunderstanding between the wishes of the appellers and the understanding of the public's target. This study aims to: (1) describe the shape of the parts of the advertisement in the form of the title, text, and slogan contained in the public services advertisement regarding Covid-19, (2) describe the form of the relationship between signs and references in the form of markers and signs in the services advertisement. the public regarding Covid-19, (3) describe and provide an overview of suggestions regarding the role of the proper meaning in public servicess about Covid-19. The research design used a qualitative design collected from research subjects in the form of public services advertisements about Covid-19 collected from websites and print media in the form of visual media. The objects in this study are in the form of words, phrases, sentences, images, and colors in these advertisements. The research stage begins with the collection of public services data about Covid-19, then a picture of the correct meaning of the advertisement for public services regarding Covid-19 will be drawn up based on semiotics. The results achieved in this study were the addition of semiotic science variables in the design of public services advertisements regarding Covid-19 so as to provide an overview of the suitability between the application of semiotics and the practice of giving advice and servicess as outlined in advertisements. The exact match between the desires and the meaning to be conveyed can be well developed to avoid misunderstandings between the advocate and the target public. Another target to be achieved in this research is the development of language knowledge in a broader realm both in the world of non-profit advertising. Keywords: semiotics, advertising, covid-19, public, services